2022
DOI: 10.1021/acsaem.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

The Abnormally Excellent Figure of Merit of 14,14,18-Graphyne at Room Temperature: A Study on the Thermoelectric Characteristic of Graphyne

Abstract: The application of carbon-based nanomaterials in the field of thermoelectric is enormously restricted for its high thermal conductivity. Graphyne, as the allotrope of graphene, expresses low thermal conductivity; therefore, it can be expected to break the limitation of carbon-based materials in thermoelectric field. By using the first-principles calculation combined with the Boltzmann theory, the thermoelectric properties of types of graphynes, i.e., 6,6,6-, 6,6,12-, 14,14,18-, and 18,18,18-graphyne, are syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 160 Due to the low efficiency of thermoelectric conversion, the application of traditional organic solid materials in flexible thermoelectric devices is greatly limited. 161 Recent studies have shown that low-dimensional materials can have higher thermoelectric conversion efficiency due to quantum confinement effects. 162 Therefore, the study of the thermoelectric properties of 2D materials has become an attractive research spot, which can not only provide powerful theoretical support for alleviating the energy and environmental crisis faced by current society but also provide theoretical models for obtaining higher-performance thermoelectric materials.…”
Section: Characteristic Properties and Related Applicationmentioning
confidence: 99%
“… 160 Due to the low efficiency of thermoelectric conversion, the application of traditional organic solid materials in flexible thermoelectric devices is greatly limited. 161 Recent studies have shown that low-dimensional materials can have higher thermoelectric conversion efficiency due to quantum confinement effects. 162 Therefore, the study of the thermoelectric properties of 2D materials has become an attractive research spot, which can not only provide powerful theoretical support for alleviating the energy and environmental crisis faced by current society but also provide theoretical models for obtaining higher-performance thermoelectric materials.…”
Section: Characteristic Properties and Related Applicationmentioning
confidence: 99%
“…15 Qi and co-workers showed higher ZT (Figure of merit) for 14,14,18-graphyne than most of the other graphynes and it can be used as a very good thermoelectric material. 16 Mortazavi et al performed detailed first-principle calculations on various substituted graphyne and graphdiyne systems (N, B, P, Al, As, Ga) for their mechanical, optical and electronic properties. 17…”
Section: Introductionmentioning
confidence: 99%
“…15 Qi and co-workers showed higher ZT (Figure of merit) for 14,14,18-graphyne than most of the other graphynes and it can be used as a very good thermoelectric material. 16 Mortazavi et al performed detailed firstprinciple calculations on various substituted graphyne and graphdiyne systems (N, B, P, Al, As, Ga) for their mechanical, optical and electronic properties. 17 Unlike pure sp 2 -sp 2 hybridization on graphene, an sp-sp 2 network in graphyne introduces voids in the system and makes it extremely attractive for storage and controlled electron-transport along C-C triple bonds.…”
Section: Introductionmentioning
confidence: 99%